Social Change and Demythologization: (A Reading of Kuntowijoyo's Novels) - Effendy, Chairil; Asrori, Muhammad (Advances in Social Sciences Research Journal, 2024)
This study attempts to read Kuntowijoyo's thoughts in five of his novels, namely Kereta Api yang Berangkat Pagi Hari (KAyBPH, 1966), Pasar (1972), Khotbah di Atas Bukit (KdAB, 1976), Mantra Pejinak Ular (MPU, 2000), and Wasripin dan Satinah (WS, 2003). Through heuristic and hermeneutic readings and analysis using a socio-historical approach, the following results were obtained. First, the five novels contain a common thread of relatively similar issues, namely social change. The first novel emphasizes social change in the village community in the post-war Sala region. It illustrates that the village community is still in the value system of "guyub rukun", although it has been infiltrated by the values of individualism. The second novel emphasizes social change with the setting of a market in Java. It depicts a society that is entering an era of madness (manners are violated, capital owners act exploitatively, government officials work at will); only those who are eling (remembering) and vigilant and understand the role of taste will survive life. The third novel emphasizes the social changes caused by development that is too physical, neglecting spiritual development, so that people lose their grip on life. The fourth novel emphasizes the social changes in the sub-district around Sala under the New Order regime. There is resistance from community members to the party's power, but it is subtle. Furthermore, in the last novel, social changes in the fishing community on the North Coast of Java under the New Order regime are also emphasized. The heavy pressure of socio-economic life gave birth to the myth of Ratu Adil. The treatment of the authoritarian regime was met with strong resistance: the community attacked and killed the security forces who engineered injustice. Secondly, socio-historically, the five novels show the development of problems in Indonesian society. Thirdly, all five novels show the details of the physical location of villages in Java, as well as the socio-cultural values of the people. Fourth, the novels show the author's response to the social life of Indonesian society from the beginning of independence to under the New Order regime.